2012
DOI: 10.1371/journal.ppat.1002509
|View full text |Cite
|
Sign up to set email alerts
|

Identification and in vitro Analysis of the GatD/MurT Enzyme-Complex Catalyzing Lipid II Amidation in Staphylococcus aureus

Abstract: The peptidoglycan of Staphylococcus aureus is characterized by a high degree of crosslinking and almost completely lacks free carboxyl groups, due to amidation of the D-glutamic acid in the stem peptide. Amidation of peptidoglycan has been proposed to play a decisive role in polymerization of cell wall building blocks, correlating with the crosslinking of neighboring peptidoglycan stem peptides. Mutants with a reduced degree of amidation are less viable and show increased susceptibility to methicillin. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 69 publications
5
113
0
Order By: Relevance
“…Recently, it was shown that the enzyme LtsA is responsible for the amidation of mDAP (46). The amidation of D-Glu is probably performed by Cg0299 and Cg0300, as shown for homologous proteins of Staphylococcus aureus (47,48). Subsequently, Lipid II is translocated across the cell membrane (step 2), where the peptidoglycan polymerization takes place.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the enzyme LtsA is responsible for the amidation of mDAP (46). The amidation of D-Glu is probably performed by Cg0299 and Cg0300, as shown for homologous proteins of Staphylococcus aureus (47,48). Subsequently, Lipid II is translocated across the cell membrane (step 2), where the peptidoglycan polymerization takes place.…”
Section: Discussionmentioning
confidence: 99%
“…In Staphylococcus aureus and Streptococcus pneumoniae where the di‐basic amino acid is L‐Lys instead of mDAP, D‐Glu is amidated to D‐iso‐glutamine. The two enzymes responsible for D‐Glu amidation (the MurT/GatD complex) have been identified (Munch et al ., 2012; Figueiredo et al ., 2012), and PG transpeptidases have been shown to work more efficiently when D‐Glu is amidated (Munch et al ., 2012; Figueiredo et al ., 2012). In B. subtilis , mDAP was found to be amidated in most muropeptides of vegetative cell PG, while D‐Glu was not amidated (Atrih et al ., 1999; Warth and Strominger, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale synthesis and purification of the peptidoglycan precursors lipid I, lipid II, lipid II-Gly 1Ϫ5 and amidated lipid II were performed as described previously (45,46). Lipid II-Asp was synthesized with purified lipid II and purified recombinant Asl-His 6 as described above using nonradioactive D-aspartate (37,38).…”
mentioning
confidence: 99%